The epidemiological and clinical features of monkeypox in human: Present global status and future management in Bangladesh - Md. Taimur Islam; Anas Bin Harun; Abdullah Al Bayazid; Shahnaz Sultana; Mirza Mienur Meher; Anup Kumar Talukder; Md. Golam Haider (Annals of Medical Science and Research)
A recent outbreak of the pandemic monkeypox has posed a deep concern to human health just following the devastating outbreak of COVID-19. The monkeypox-infected patient was detected in England on May 7, 2022. Here, we aimed to describe the epidemiology, pathogenesis, treatment, and diagnosis of monkeypox with the global responses to tackle this dreadful disease, particularly on how Bangladesh can deal with this disease having limited resources. To date, a total of 85,158 people are officially reported as monkeypox infected with 88 deaths. To combat this disease, various steps have been taken globally such as diagnosis of the suspected cases, vaccination programs, antiviral drug therapy, frequent reporting of the cases, restrictions on animal trade, quarantine of suspected people, isolation of infected patients, increase public awareness, and global collaboration. Moreover, we attempted to provide some guidelines to restrict this deadly disease in Bangladesh, highlighting the current challenges of this disease.